Blood testing in sport: Hematological profiling - Kuipers, H.; Dubravcic-Simunjak, S.; Moran, J.; Mitchell, D.; Shobe, J.; Sakai, H.; Ambartsumov, R. (International Journal of Sports Medicine, 2010)
Hemoglobin concentration and percent reticulocytes (%retics) were analyzed in blood samples taken pre-competition, post-competition, and during out of competition testing in elite speed skaters. Percent reticulocytes during screening was not different from the values obtained post-race, and no significant gender difference was found. Mean hemoglobin concentration both in males and females was slightly higher at 1 425 m altitude compared to <750 m altitude (0.23 g/dl increase in males and 0.48 g/dl increase in females; p<0.05 and p<0.01, respectively). Mean %retics at 1 425 m altitude is higher (0.24% in males and 0.27% in females, respectively, p<0.01) compared to blood sampled <750 m altitude. The distribution of percent reticulocytes shows 11 out of 11 500 samples with %reticulocytes below 0.4%. From the 171 samples with a values >2.4% in 52 skaters at least two consecutive samples yielded a percent reticulocytes above 2.4%. In 50 individuals with generally normal values but at least in two consecutive samples values above 2.4% the pattern required additional testing. In conclusion, percent reticulocytes are a robust hematological parameter, including acute exercise.